Sewage Sludge Application in Eucalyptus urograndis Plantation: Availability of Phosphorus in Soil and Wood Production - Abreu-Junior, Cassio Hamilton; Oliveira, Marcelo Gomes de; Cardoso, Paulo Henrique Silveira; Mandu, Thays da Silva; Florentino, Antonio Leite; Oliveira, Fernando Carvalho; Reis, Josimar Vieira dos; Alvares, Clayton Alcarde; Stape, José Luiz; Nogueira, Thiago Assis Rodrigues; Capra, Gian Franco; He, Zhenli (Frontiers in Environmental Science, 2020)
Phosphate fertilizers used in planted forests mainly come from scarce and non-renewable sources, and there is a need for new sources of phosphorus (P). An alternative is the use of sewage sludge (SS), rich in organic matter, nitrogen and P. The objectives were to evaluate the soil P availability and its effect on wood production in 22-months old Eucalyptus urograndis plantation treated with SS. A field experiment was set up in a randomized complete block design, four replicates, with the following treatments: control without fertilization; mineral fertilization (MF); 14.5 Mg ha-1 of SS + 22 kg ha-1 of P (S1P1); 29 Mg ha-1 of SS (S2); 29 Mg ha-1 of SS + 17.5 kg ha-1 of P (S2P2); and 43.5 Mg ha-1 of SS (S3), dry base. Of total P in SS, 65% was in organic form, and 42% was in labile + moderately labile forms. S2P2 and S3 positively altered the pattern of soil P distribution, with more P in the labile and moderately labile fractions than non-labile fraction, along 0-20 cm depths, than MF and control. There were higher microbial and available P as a function of SS dose. Wood volume and biomass were highly related to soil P availability as a function of SS dose. Within the SS treatments, S2P2 resulted in higher gains of volume and biomass of wood. The SS application at recommend rate, supplemented with 66% of recommended P fertilizer dose in Eucalyptus plantations, can reduce the use of P fertilizer by 33%, N fertilizer by 100% and maintain comparable soil P availability and wood production.